Adsorption Of Chloramphenicol By Ordered Mesoporous Carbons Using Aspen Simulation - Mohammad Nasruddin, Muhammad Alif Aiman (Universiti Sains Malaysia, 2021)
Chloramphenicol (CAP) is found abundance in composition of water that hazardous and cause harmful to human health if consume and to ecosystem. Therefore this study is about the adsorption/removal of chloramphenicol by ordered mesoporous carbons (OMC) using the Aspen Adsorption® simulation. First and foremost in the simulation, the constant parameters need to be identified and manual calculated in the Microsoft Excel such as isotherm parameters (IP) values, adsorbent and bed porosity, tortuosity and the global mass transfer coefficient (MTC). The first simulation operation condition are manipulating the initial CAP concentration (50, 100 & 200 mg/L) and constant the bed height (2cm) and flowrate (10 mL/min). At 50 mg/L initial concentration show the longest breakthrough (925 minutes) and exhaustion time (1600minutes). For the changing in the flowrate (10, 20 & 30 mL/min), the longest breakthrough and exhaustion time is at 10 mL/min which 925 minutes and 1600 minutes respectively. Vice versa for the effect of the bed height (2, 4 & 6 cm) on adsorption, which show the longest breakthrough (2700 minutes) and exhaustion time (4500 minutes) at 6 cm. In the simulation column adsorption studies, Thomas and Yoon-Nelson model shows the highest R2 value (0.999) compared to Bohart-Adams model (0.950-0.99).